PENINGKATAN KESEJAHTERAAN TENAGA KERJA DALAM UNDANG-UNDANG CIPTA KERJA BERDASARKAN TEORI HUKUM PEMBANGUNAN - Herriyanto, Fajar; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Ensiklopedia of Journal, 2025)
Abstract: The Law of Job Creation is a strategic step of Indonesian Government to improve the economy through investment and accelerate job creation. However, government needs to ensure that basic labor rights are not ignored. The main problem is whether the Job Creation Law answers the modern employment challenges, such as job security, flexibility, welfare and labor rights protection. This research is expected in contributing to the Indonesian laws, as well as providing policy recommendations to ensure that legal reforms are truly promote labor welfare. A qualitative method with approach of normative and descriptive analysis with the main data source coming from laws and regulations are used in this research. Quantitative methods are used to analyze the Job Creation Law impact. Judging from the empirical data, there was a decrease in the wage,  failure to reduce the unemployment rate and reduce labor welfare after the Law’s implementation. The Law does not fully reflect the principles of development law, especially in protecting labor welfare. Although this law encourage economic growth through increased investment, several provisions that weaken labor protection must be reconsidered. There are many shortcomings in the Law’s implementation and can only be successful if it provides positive impacts on the welfare of the workforce.Keywords: Job Creation Law, Labor, Welfare, Development